2014
DOI: 10.1021/jp4091969
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and Viscoelastic Properties of Cross-Linked Gold Nanoparticles Probed by AFM Bulge Tests

Abstract: To enable applications of nanoparticle films in flexible electronics, actuators, and sensors, their mechanical properties are of critical concern. Here, we demonstrate that the elastic and viscoelastic properties of covalently cross-linked gold nanoparticles (GNPs) can be probed using AFM bulge tests. For this purpose 30−60 nm thick films consisting of 1,9-nonanedithiol (NDT) cross-linked GNPs (3.8 nm core diameter) were transferred onto substrates with ∼100 μm circular apertures. The resulting freestanding me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(89 citation statements)
references
References 36 publications
6
83
0
Order By: Relevance
“…23 In good agreement with the experimental results, 14 it is based on the assumption of a spherical bulge geometry.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…23 In good agreement with the experimental results, 14 it is based on the assumption of a spherical bulge geometry.…”
supporting
confidence: 72%
“…1−6 Further, these materials enable the costefficient fabrication of devices via laser writing, printing, and self-assembly techniques on various substrates. 7−11 Recently, the mechanical properties of freestanding membranes comprised of ligand-stabilized gold nanoparticles (GNPs), 12,13 cross-linked GNPs, 14 or polymer/GNP composites 15 have been studied in different laboratories using atomic force microscopy (AFM) indentation or micro bulge tests. These investigations showed that GNP membranes are mechanically surprisingly robust.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An increasingly important application of the Atomic Force Microscope (AFM) is the characterization of viscoelastic materials and interfaces, such as cell membranes and tendons [1][2][3][4], polymer blends and composites [5][6][7][8][9][10][11], the liquid-gas and liquid-solid interfaces [12,13], and suspended membranes [14]. The present trend toward higher scanning speeds [15,16] and higher resolution mapping of mechanical properties [17,18] necessitates more rapid tip motion and therefore a larger viscous contribution to the tip-sample force.…”
Section: Introductionmentioning
confidence: 99%
“…Assemblies of ligand-stabilized noble metal nanoparticles are of great interest because of their unique optical, 1 electrical 2 and mechanical 3,4 properties, which all can be tuned by varying the materials' composition and structural parameters. This provides the opportunity to tailor materials with desired properties for various specic applications like resistive [5][6][7] or optical 8,9 strain and vapor sensing, catalysis, 10 nanoelectromechanical systems, 11,12 and surface enhanced Raman scattering.…”
Section: Introductionmentioning
confidence: 99%